Increased Production and Flavonoids of Two Celery Highland Varieties (Apium graveolens L.) by Endophytic Bacteria in Lowland - Andika Akbarul Iman; Sandra Arifin Aziz; Abdul Munif (AGRIVITA, Journal of Agricultural Science, 2023)
Celery (Apium graveolens L.) is an annual plant that grows optimally in Indonesiaâ€™s highlands. The provision of endophytic bacteria has the role of plant protection, increasing agronomic growth and plant physiology, and overcoming environmental stresses. This study aims to assist the adaptation of highland celery varieties in the lowlands due to the decreasing agricultural highland and increase their production with endophytic bacteria applications.Â The experiment was executed in Bogor, Indonesia using a randomized block design with two factors. The celery variety served as the first factor [Amigo and Aroma (highland variety), and Summer Green (lowland variety)], and endophytic bacteria was the second factor (control, APE35, a combination of APE35+BAT, APE35+BAT+EQ26, and the PTM3 consortium). The result showed that endophytic bacteria helped the plants to adjust growth from highland to lowlands and increase yield. In lowland, Amigo showed shorter in height but it has a significantly higher stalk number, carotenoids, and flavonoids than Summer Green (lowland control). Endophytic bacteria increased plant growth, N, P, pigments, and flavonoids. APE35 or PTM3 with Amigo produced significantly higher leaf area, number of tillers, number of leaflets, leaf area, head fresh weight (78.529 and 75.054 g/plant), total fresh weight (81.67 and 85.395 g/plant), and total flavonoids (1484.818 and 1502.459 mg QE/100 g) than Summer Green without endophytic bacteria.